Response to Edmund N. Santurri. Issue 3 (18th July 2013) - Novak, David
Abstract Barth and Niebuhr seemed to be wary of natural law because each of them thought that the "natural" in natural law means that natural law has to be rooted in natural theology. However, natural law today is more cogently formulated without any natural theology at all. "Natural law" means that law can be derived from the twofold character or nature of human personhood: the capacity for a communal relationship with other humans, and the capacity for a covenantal relationship with God, both of which continually overlap in human life. The natural or external world only provides the backdrop for these human capacities; it does not determine them.